Unveiling the impact of modified cell death models on hypofractionated radiation therapy efficacy; Biomedical Physics & Engineering Express; Vol. 11, iss. 6 - Sagov I. R. Islam Ruslanovich; Sorokina A. A. Aida Arsenovna; Sukhikh E. S. Evgeniya Sergeevna; Selikhova E. A. Ekaterina Alexandrovna; Kirpichev Yu. S. Yury Sergeevich (2025, 2025)
Title screen